Age at natural menopause and risk of incident cardiovascular disease: a pooled analysis of individual patient data. (November 2019) - Zhu, Dongshan; Chung, Hsin-Fang; Dobson, Annette J; Pandeya, Nirmala; Giles, Graham G; Bruinsma, Fiona; Brunner, Eric J; Kuh, Diana; Hardy, Rebecca; Avis, Nancy E; Gold, Ellen B; Derby, Carol A; et al.
Summary: Background: Early menopause is linked to an increased risk of cardiovascular disease mortality; however, the association between early menopause and incidence and timing of cardiovascular disease is unclear. We aimed to assess the associations between age at natural menopause and incidence and timing of cardiovascular disease. Methods: We harmonised and pooled individual-level data from 15 observational studies done across five countries and regions (Australia, Scandinavia, the USA, Japan, and the UK) between 1946 and 2013. Women who had reported their menopause status, age at natural menopause (if postmenopausal), and cardiovascular disease status (including coronary heart disease and stroke) were included. We excluded women who had hysterectomy or oophorectomy and women who did not report their age at menopause. The primary endpoint of this study was the occurrence of first non-fatal cardiovascular disease, defined as a composite outcome of incident coronary heart disease (including heart attack and angina) or stroke (including ischaemic stroke or haemorrhagic stroke). We used Cox proportional hazards models to estimate multivariate hazard ratios (HRs) and 95% CIs for the associations between age at menopause and incident cardiovascular disease event. We also adjusted the model to account for smoking status, menopausal hormone therapy status, body-mass index, and education levels. Age at natural menopause was categorised as premenopausal or perimenopausal, younger than 40 years (premature menopause), 40–44 years (early menopause), 45–49 years (relatively early), 50–51 years (reference category), 52–54 years (relatively late), and 55 years or older (late menopause). Findings: Overall, 301 438 women were included in our analysis. Of these 301 438 women, 12 962 (4·3%) had a first non-fatal cardiovascular disease event after menopause, of whom 9369 (3·1%) had coronary heart disease and 4338 (1·4%) had strokes. Compared with women who had menopause at age 50–51 years, the risk of cardiovascular disease was higher in women who had premature menopause (age <40 years; HR 1·55, 95% CI 1·38–1·73; p<0·0001), early menopause (age 40–44 years; 1·30, 1·22–1·39; p<0·0001), and relatively early menopause (age 45–49 years; 1·12, 1·07–1·18; p<0·0001), with a significantly reduced risk of cardiovascular disease following menopause after age 51 years (p<0·0001 for trend). The associations persisted in never smokers, and were strongest before age 60 years for women with premature menopause (HR 1·88, 1·62–2·20; p<0·0001) and early menopause (1·40, 1·27–1·54; p<0·0001), but were attenuated at age 60–69 years, with no significant association observed at age 70 years and older. Interpretation: Compared with women who had menopause at age 50–51 years, women with premature and early menopause had a substantially increased risk of a non-fatal cardiovascular disease event before the age of 60 years, but not after age 70 years. Women with earlier menopause need close monitoring in clinical practice, and age at menopause might also be considered as an important factor in risk stratification of cardiovascular disease for women. Funding: Australian National Health and Medical Research Council.